TÜRKİYE - Ilknur Yücel; Nadiye Camci (KHD Production, 2024)
This study was conducted to examine nursing graduate thesis studies in order to evaluate the effect of professional care provided by nursing professionals on the quality of life of individuals in Turkey. In this study, master's and doctoral theses registered in the archive of the Thesis Center of the Council of Higher Education were examined, and a scan was made with the words